The leucocytes, neutrophils and superoxydes dismutase (SOD) level after consuming guava juice (Psidium guajava L) during aerobic exercise for beginners - Zaenal Muttaqien Sofro, Yuliana Noor Setiawati Ulvie Wiryatun Lestariana (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2014)
Physical exercise is important in preventing and adjunctive therapy certain diseases. However,over physical exercise for beginners may cause oxidative stress and muscle injury leads to generatechemoattractants whic enables to attract neutrophil and monocyte towards the injury and stimulatesleucocytes activation. The use of antioxidant-rich fruits to mitigate exercise induced oxidative stresshas been applied. This study was conducted to evaluate the effect of guava juice (Psidium guajavaL) consumption during aerobic exercise on leucocytes, neutrophils and superoxydes dismutase(SOD) level of beginners. Sixteen students of National Land College (Sekolah Tinggi PertanahanNasional/STPN), Yogyakarta who met the inclusion and exclusion criteria were involved in thisstudy. Subjects were divided into two groups i.e. a group given mineral water as control andanother group given 240 mL guava juice 0.67 g/mL daily for 27 days as treatment group. Bothgroups then underwent aerobic exercise for 30 minutes every day for 27 days. Blood samples weretaken before and after exercise on day 1, 7 and 14 for leucocyte and nutrophil count as well as SODanalysis. The leucocyte count and SOD level before and after exercise in both Guava juice andMineral water groups were not significantly different (p>0.05). However, the percentage of neutrophilon day 1 and 7 were significantly higher than that in Mineral water group (p<0.05). Moreover,during the exercise, the percentage of neutrophils in Guava juice group significantly increased(p<0.05), whereas in Mineral water group was not significantly different (p>0.05). It can beconcluded that consuming guava juice during exercise for the beginners does not influence leucocytecount and SOD levels. However, it can increase percentage of neutrophil.